The influence of static and progressive stretching exercises on the functional limitations of the musculoskeletal system - Boguszewski, Dariusz; Radomska, Agnieszka; Kerbaum-Visser, Katarzyna; Białoszewski, Dariusz (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The main objective of the study was to assess the effectiveness of a warm-up programme that incorporated static and progressive stretching exercises in minimising the functional limitations of the locomotor system. Materials and Methods. The study consisted of 70 women and 18 men. The subjects performed Functional Movement Screen (FMS) and Core Muscle Strength and Stability Test (CMS&ST) twice. The first, it did not include warm up, which was in accordance with the authors’ recommendations. Next, after a week, students were randomly divided into two groups and the tests were carried out again. Before the second examination Group I performed warm-up with static stretching exercises, while Group II did a warm-up consisting of progressive stretching exercises. The students participating in the study were also asked to fill a custom survey. The Mann-Whitney U test was used to evaluate the differences between the groups, and the Wilcoxon’s test was used to evaluate the differences between the measurements, with minimal statistical significance set at p ≤ 0.05. Results. The study showed that static and progressive stretching has a positive impact on minimising the functional limitations of the locomotor system measured with the Functional Movement Screen test. The differences between the first and the second measurement in the women’s Group I and II, and the men’s Group I and II were statistically significant. (Group I women – p < 0.001; Group II women – p < 0.001; Group I men – p < 0.001; Group II men –p = 0.003). Conclusions. Both static and progressive stretching may have a positive impact on minimising the functional limitations of the locomotor system. It is desirable to incorporate that kind of exercises into the supplementary training plan (warm-up/suplementary exercises).
Keywords: stretching; FMS; injury prevention; functional assessment